2020
DOI: 10.3892/etm.2020.8861
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between fecal calprotectin, ulcerative colitis endoscopic index of severity and clinical outcome in patients with acute severe colitis

Abstract: Correlation between fecal calprotectin (FC) and endoscopic activity assessed by Ulcerative Colitis Endoscopic Index of Severity (UCEIS) in acute severe colitis (ASC) patients was explored to evaluate the predictive value of FC in clinical outcomes. Seventy-one ASC patients were retrospectively evaluated. FC level within 3 days of colonoscopy was measured with ELISA. Demographic and clinical data, laboratory parameters, and medical therapy were documented, and the endoscopic severity of disease was rated by UCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Other studies showed that low serum albumin and high CRP levels are associated with severe disease activity in patients with ulcerative colitis [ 21 ]. Furthermore, a correlation was found between fecal calprotectin and clinical outcome in patients with ulcerative colitis [ 22 ]. These findings warrant further study to find the role of FC as a prognostic marker in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that low serum albumin and high CRP levels are associated with severe disease activity in patients with ulcerative colitis [ 21 ]. Furthermore, a correlation was found between fecal calprotectin and clinical outcome in patients with ulcerative colitis [ 22 ]. These findings warrant further study to find the role of FC as a prognostic marker in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Second, endoscopic features and laboratory data are currently routinely involved in the diagnosis and decision-making of clinicians, which could introduce circularity of argument, an inevitable inherent issue in data interpretation, and a prospective study may help in the future [ 27 ]. Moreover, in addition to endoscopic features and laboratory data, many novel predictors for IVCS response in UC patients have been proposed, including fecal calprotectin levels [ 36 , 37 ] and histological indices [ 38–40 ]. These factors were not recorded in our study due to restrictions of objective conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In another retrospective Chinese cohort of 71 ASUC patients, faecal calprotectin levels >1672 µg/g on day 3 after colonoscopy predicted colectomy with a sensitivity of 80.2% and a specificity of 66.7%. 14 Elevated serum CRP levels at day 3 (>9.9 mg/dL) were also associated with steroid failure in a prospective paediatric cohort of 128 children. 15 Elevated serum procalcitonin levels (>0.10 µg/L) were found to be a predictor for corticosteroid failure and colectomy in a retrospective study of 151 ASUC patients.…”
Section: Challenges Associated With Asuc Managementmentioning
confidence: 97%